Design and Build a Network Security System Using Port Knocking, DMZ and IDS Techniques at SMA Negeri 1 Warungkiara - Somantri Somantri; Rahman Zulkarnaen; Gina Purnama Insany (Universitas Medan Area, 2023)
The network security system of SMA Negeri 1 Warungkiara needs improvement to be more effective in safeguarding data integrity and confidentiality. Currently, it only relies on a filter rule security, which is not robust enough to fend off hacker attacks. Therefore, advanced security techniques such as Port Knocking, DMZ, and IDS are required. Port Knocking serves as additional authentication by accessing ports in a specific sequence to prevent unauthorized access. DMZ is used to isolate the internal network from direct attacks. IDS is used to detect suspicious activities and alert the administrator. The system was tested against various attacks such as port scanning, DDoS, and Ping of Death, and it was proven to reduce server resource usage from 34% to 6%. The test results show that this security system provides strong protection and preserves the integrity and confidentiality of data within the school network.